Poverty of Energy and Its Impact on Living Standards in Ethiopia - Elias Mandefro Getie (Journal of Electrical and Computer Engineering)
Energy is the backbone of the economic development of a country. Ethiopia has bulk energy resource potential, and the effect of energy poverty on well-being, physical health, agriculture automation, education system, industries, and ability to prosper is valuable. A large proportion of the population living in Ethiopia has no electricity access. Among more than 110 million people living in Ethiopia, 46% only use electric energy for day-to-day activities like food preparation and other tasks. In the rural area of the country, where 80% of the population lives, people have no sustainable energy supply. The rural electrification needs special mechanisms to enhance the living standards of the people by opening opportunities for electric power infrastructures. The sustainable development of the country will be achieved when citizens are enabled to live up to the standard of living as humans. This paper investigates energy poverty in Ethiopia and its impact on the living standards of the people, like human resource development, health of individuals, and automation of agriculture, for the purpose of upgrading individual’s lifestyle in the country.